The role of private natural heritage conservation areas in promoting sustainable development Goals Insight - Yunhai Zhao; Muhammad Umair; Fatima Gulzar; Shafa Guliyeva; Dadajon Xabibullayev (Ecological Indicators)
Private Natural Heritage Reserves (PNHRs) in Brazil are increasingly viewed as decentralized instruments for sustainability governance, yet their function as territorial indicators of socio-environmental performance remains underexplored. This study investigates the extent to which PNHRs can serve as localized barometers of sustainability, with an emphasis on the environmental functions and socio-economic engagements that reflect core principles of the 2030 Agenda. Drawing on spatial and categorical assessment techniques across varying biomes and governance types, the research identifies patterns in reserve-level management behaviors that correspond with strategic sustainability targets, including watershed protection, biodiversity maintenance, and health-related ecosystem services. Through a comparative analysis of motivations, usage profiles, and governance models, the study finds that PNHRs provide a functional interface between conservation practice and sustainable development imperatives—operating as both custodians of ecological integrity and enablers of human well-being. These findings support the recognition of PNHRs as embedded, place-based systems capable of indicating progress in integrated conservation-development efforts and inform policy on enhancing their strategic role in sustainability monitoring and territorial planning.